2002
DOI: 10.1039/b208868a
|View full text |Cite
|
Sign up to set email alerts
|

Calibration errors due to variations in peak characteristics in the measurement of transient signals by inductively coupled plasma-scanning mass spectrometry

Abstract: The impact of variations in peak characteristics on the fidelity of transient signal measurement by inductively coupled plasma-quadrupole mass spectrometry (ICP-QMS) was investigated. Specifically, the question as to whether the multi-element capabilities or the accuracy in determined analyte amounts were deteriorated compared to what has been reported previously when not considering peak variations was addressed. The peak characteristics considered were the time of the signal maximum (t peak ), the standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Several researchers have shown the isotope-ratio precision obtainable with quadrupole [26,28] and double-sector [29] ICP-MS instruments to improve as the time between successive m/z observations is reduced. Bjorn et al [20] have also shown the isotope ratio precision to be a function of the order in which m/z are observed.…”
Section: Inductively-coupled Plasma Mass Spectrometrymentioning
confidence: 95%
See 2 more Smart Citations
“…Several researchers have shown the isotope-ratio precision obtainable with quadrupole [26,28] and double-sector [29] ICP-MS instruments to improve as the time between successive m/z observations is reduced. Bjorn et al [20] have also shown the isotope ratio precision to be a function of the order in which m/z are observed.…”
Section: Inductively-coupled Plasma Mass Spectrometrymentioning
confidence: 95%
“…Because there is a fundamental limit to the rate at which successive measurements can be made with these instruments, a compromise is often made to limit the number of masses that are observed during each transient, or by approximating a steady-state situation by diluting a transient to extend its duration [18,19]. Recently, several investigators have accomplished quantitation of transient events in ICP-MS by collecting as few as three to four points across each transient profile, sacrificing peak-shape information in order to observe a greater number of m/z values [20][21][22]. The authors note, however, that care must be taken in applying this under-sampling technique, which is best suited to the analysis of relatively imprecise single-channel measurements and to transients with symmetric peak shapes [23].…”
Section: Inductively-coupled Plasma Mass Spectrometrymentioning
confidence: 98%
See 1 more Smart Citation
“…By contrast, Bjo¨rn et al 12 have suggested that to obtain calibration slopes with less than 1% standard deviation it is necessary to acquire 7 to 24 data points to characterize a typical ETV peak using a 5 to 50 ms dwell time. This would limit the number of mass-to-charge ratios that could be monitored to between 4 and 10 with QMS detection.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] It has been argued that the nature of scanning instruments is not optimal for such multi-element measurements; as the number of ions of interest increase, the dwell time for each isotope decreases in order to preserve temporal signal information. As well, fluctuations in the rate of sample introduction and plasma noise restrict high precision isotope ratio measurement capability.…”
Section: Introductionmentioning
confidence: 99%